The human condition - Kekes, John.; Kekes, John.; Kekes, John. (Oxford : Oxford University Press, 2010)
John Kekes offers a response to the growing disenchantment in the Western world with contemporary life. He defends a realistic view of the human condition that rejects both facile optimism & gloomy pessimism. While acknowledging that the scheme of things is indifferent to our fortunes, he shows that we do have the resources to improve our lives.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Life; Meaning (Philosophy)